Adverse effects of the automotive industry on carbon dioxide emissions - Bosupeng, Mpho (The European Journal of Applied Economics, 2016)
This study aims to determine the effects of the automotive industry on carbon dioxide emissions for the period from 1997 to 2010 for diverse economies, as well as the relationships between carbon dioxide discharges and output. The study applies cointegration and causality tests to validate these associations. The results of the Johansen cointegration test depict long-run associations between the quantity of passenger cars and carbon dioxide emissions in France, Sweden, Spain, Hungary and Japan. In addition, significant relations were observed between output and carbon dioxide discharges in Spain, Canada, India and Japan. Changes in output had substantial impact on emissions in Germany, Canada and India. The results also show that the number of passenger cars influences the magnitude of emissions in multiple economies. In conclusion, the automotive industry has to be considered in policies that aim to reduce carbon dioxide emissions.
Keywords: automotive industry; economic growth; carbon dioxide emissions